What's up, Doc? [videorecording (DVD)] - Bogdanovich, Peter, 1939-; Streisand, Barbra; O'Neal, Ryan; Mars, Kenneth; Pendleton, Austin; Booke, Sorrell, 1930-1994; Murphy, Michael, 1938-; Kahn, Madeline; Kovács, László, 1952- (Streisand collection., 2003)
Four red plaid traveling cases-- one of each belonging to a befuddled Iowa musicologist, a strange but bright young woman, a rich matron and a suspicious fellow-- are mixed up at a San Francisco hotel, with hilarious results.